EKSPRIMENTAL PENGUKURAN KEPADATAN BASE COURSE DENGAN ALAT SAND CONE DAN NUCLEAR DENSITOMETER TEST - Supardin Supardin; Teuku Riyadhsyah; Risma Agustina (Politeknik Negeri Lhokseumawe, 2011)
Material or base course pavement material consists of aggregate based on the well proportioned so that the density obtained in provides support on the road. This study aims to measure the achievement of the density of base course with a sand cone and nuclear densitometer. Case studies carried out on the road Banda Aceh - Calang along 1 km from sta 76 +510 s / d 77 +650 with the testing interval is 50 m. The results of the sand cone test parameters such as: water content (w) = 6.34%, by weight content of the soil (∂ b) = 2.36 gr/cm3, dry unit weight (∂ d) = 2.25 gr/cm3, Volume holes = 1671.68 gr/cm3 and the degree of density (Dr) = 99.60%, while the nuclear densitometer test results such as: water content (w) = 4.12%, by weight content of the soil (∂ b) = 2.38 gr/cm3, dry unit weight (∂ d) = 2.41 g / cm3, and the degree of density (Dr) = 100.01%. Validation of measurements according to sig. (2-tailed), ie 0546 0050 α, then there is no significant difference in density between the two tools. Results of testing sand cone and nuclear densitometers have 0.4% difference, then both the above test methods can be used. The advantage when using sandcone time it takes relatively longer and cost less, while for the testing of nuclear densitometer test time required faster and more expensive.Keywords: density, sandcone and nuclear densitometer